TINJAUAN YURIDIS KEDUDUKAN MEDIATOR BERSERTIFIKASI KAITANNYA DENGAN PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2008 DALAM MENYELESAIAN SENGKETA TANAH DI PENGADILAN NEGERI SAMARINDA - Omcitra Situmeang (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTAs time goes on, humans are increasing, and even the need for shelter is getting higher and the availability of land will be less. So, the problem of land problems will be higher and the number will increase. It is better in rural areas and more so in urban areas. business requires efficiency and harmony as well as the continuation of cooperative and formalistic relations and requires solutions that emphasize justice, ligitation institutions cannot respond because in operation they are considered to be slow and wasteful of energy, time and money. Therefore dispute resolution through litigation or court, often does not resolve the problems raised by the parties, the Ligitation cannot provide a win-win solution, so it starts to be seen as the last attempt to resolve the dispute. Thus disputes over land. as an intermediary in the problem of land disputes. Mediation is a negotiation process to solve problems and obtain agreement by the parties to the dispute. Keywords: Mediator, Land Dispute